The effectiveness of pre-tests and post-tests for teaching industrial ecology in an engineering management program - Arianti, Santi Febri (Institute of Computer Science (IOCS), 2024)
This study aims to evaluate the effectiveness of using pre-tests and post-tests combined with interactive teaching methods to enhance student engagement and understanding in an Industrial Ecology course within an Engineering Management program. Given the theoretical nature of the subject matter, this research seeks to address student disengagement and boredom by integrating regular assessments and group activities. The study was conducted with a cohort of students enrolled in the Industrial Ecology course. A structured lecture format was employed, incorporating pre-tests at the beginning of each class, followed by theoretical presentations, post-tests, and interactive group assignments. The pre-test and post-test questions were identical to assess retention and attention. Student engagement was measured through participation rates, test scores, and feedback surveys. Group activities were designed to foster discussion and critical thinking, with peer evaluations conducted to ensure active participation. The results indicated a significant improvement in student engagement and understanding. The average post-test scores increased by 20% compared to pre-test scores, demonstrating enhanced retention of the material. Student feedback revealed a higher level of interest and motivation, attributing it to the interactive and structured nature of the classes. The novelty of this approach lies in the systematic use of pre-tests and post-tests to maintain attention and the integration of interactive elements to counteract theoretical boredom, offering a practical solution for similar educational contexts.